Public greenspace and life satisfaction in urban Australia - Ambrey, Christopher; Fleming, Christopher (My University, 2013)
This paper examines the influence of public greenspace on the life satisfaction of residents of Australia’s capital cities. A positive relationship is found between the percentage of public greenspace in a resident’s local area and their self-reported life satisfaction. On average, it is found that a resident has an implicit willingness-to-pay of $1,168 in annual household income for a one per cent (143m2) increase in public greenspace. The relationship between public greenspace and life satisfaction however, is non-linear. Additional results suggest that the value of greenspace increases with population density and that lone parents, the less educated and those living in high rise dwellings benefit to a greater extent from the provision of public greenspace than the general population. In all, life satisfaction data supports existing evidence that public greenspace is welfare enhancing for urban residents and adequate allowance should be made for its provision when planning urban areas.
Keywords: Satisfaction -- Life; Housing; Housing, communities and neighbourhoods; Lifestyle; Satisfaction; Housing; Life; Lifestyle; Housing, communities and neighbourhoods